Political Power and the Process of Curbing Political Violence: A Conceptual Interpretation of Political Power’s Meaninizing, the Kurdistan Region as a Model - Sardar Qadir Muhiddeen (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
There is an essential and self-evident truth about political power in the world of politics and public affairs of societies, namely: that the existence of power did not depend on the complete satisfaction of people, nor did it stop its formation as a complete and just authority, but rather a societal necessity even if it was negative for its societies, This is the condition of human beings since ancient times, so that they have not given up political power for even a certain moment, because power is in exchange for power, there is chaos. This does not mean by us that power, whatever its type, must be satisfied with its outcome and judgment, but rather we go beyond this fact to explaining another truth that has become an example for everyone, and that if it does not examine the authority, there is no administrative prestige, supervision and law, and it must develop itself until it reaches the stage of satisfaction of the majority of people about her. Authority must be a developmental and developmental project for society, despite its necessity for society, it must try to achieve the goals of society and lead it towards perfection and the attainment of glory. Wherever the authority is found, there must be law, stability, security and progress for the better. One of its first functions is security and stability in society, because without security there is no proper authority, and there is no security, welfare and justice, so we can say that if the authority is correct everything will be reconciled in society, because the overwhelming majority of temptations come through authority and nothing else. No society in the world is free and suffers from violence to a limited extent, especially political violence, except for societies in which democracy, prosperity and justice, as these three pillars bear positive fruits on society and power. I am not afraid of any of us that the political violence prevalent in our societies, the majority of its causes come through political power, because political power has not yet been refined, suffers from many shortcomings, and has not reached a certain stage that separates political groups from their own interests. Power has become a privilege for those who find it, but whoever carries National responsibility towards society and the pursuit of prosperity and stability for society. Societies in the developing world are constantly shifting in place. Finally, regarding the Kurdistan Region of Iraq, although the authority is on its way to stability through the democratic process, it has not yet reaped the Kurdish society from its fruits, and we can say that political violence in the region decreases day after day if the authority is at the required level and is close to its introspection at the level of The concerns of the Kurdish people, and the people must feel that they have the authority to protect and direct them to achieve their goals and aspirations, and to avoid them from misfortunes, strife and crises.